Adenoviral VEGF-DΔN ΔC gene therapy for myocardial ischemia - Pajula, Juho; Lähteenvuo, Johanna; Lähteenvuo, Markku; Honkonen, Krista; Halonen, Paavo; Hätinen, Olli-Pekka; Kuivanen, Antti; Heikkilä, Minja; Nurro, Jussi; Hartikainen, Juha; Ylä-Herttuala, Seppo (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Cardiovascular diseases are the leading cause of death globally. In spite of the availability of improved treatments, there is still a large group of chronic ischemia patients who suffer from significant symptoms and disability. Thus, there is a clear need to develop new treatment strategies for these patients. Therapeutic angiogenesis is a novel therapy method which has shown promising results in preclinical studies. In this study, we evaluated safety and efficacy of adenoviral (Ad) VEGF-DΔNΔC gene transfer for the treatment of myocardial ischemia in a pig model. Methods: Adenoviral VEGF-DΔNΔC gene transfer was given to pigs (n=26) via intramyocardial injections using an electromechanical injection catheter. Angiogenic effects were evaluated in an acute myocardial infarction model (n=18) and functionality of the lymphatic vessels were tested in healthy porcine myocardium (n=8). AdLacZ was used as a control. Results: AdVEGF-DΔNΔC induced safe and effective myocardial angiogenesis by inducing a four-fold increase in mean capillary area at the edge of the myocardial infarct six days after the gene transfer relative to the control AdLacZ group. The effect was sustained over 21 days after the gene transfer, and there were no signs of vessels regression. AdVEGF-DΔNΔC also increased perfusion 3.4-fold near the infarction border zone relative to the control as measured by fluorescent microspheres. Ejection fraction was 8.7% higher in the AdVEGF-DΔNΔC treated group 21 days after the gene transfer relative to the AdLacZ control group. Modified Miles assay detected a transient increase in plasma protein extravasation after the AdVEGF-DΔNΔC treatment and a mild accumulation of pericardial effusate was observed at d6. However, AdVEGF-DΔNΔC also induced the growth of functional lymphatic vasculature, and the amount of pericardial fluid and level of vascular permeability had returned to normal by d21. Conclusions: Endovascular intramyocardial AdVEGF-DΔNΔC gene therapy proved to be safe and effective in the acute porcine myocardial infarction model and provides a new potential treatment option for patients with severe coronary heart disease.